Morphological quality of fruits and endocarps of red nanche (Malpighia mexicana, Malpighiaceae) - Maldonado Peralta, María de los Ángeles; García de los Santos, Gabino; García Nava, José Rodolfo; Corona Torres, Tarsicio; Cetina Alcalá, Víctor Manuel; Ramírez Herrera, Carlos (Instituto de Ecología, A.C., 2016)
Background and Aims: Wild red nanche develops in both temperate and tropical areas. In Mexico, it has been used as an ornamental and medicinal plant since pre-Hispanic times; however, little is known about its morphology. Therefore, the aim of this research was to characterize the morphological quality of fruits and endocarps of red nanche collected in the Central Valleys of Oaxaca, Mexico.Methods: Three study areas were located, but fruits were found in the municipality of Santiago Matatlán only. These were collected and transferred to the Seed Analysis Laboratory of the Colegio de Postgraduados, Campus Montecillo. For evaluation of the morphological quality of fruit and endocarps, four replications of 100 fruits were selected by Completely Randomized Design (CRD). With the obtained data, an analysis of measures of central tendency was performed using the SAS statistical package.Key results: The results indicated that the fruits of red nanche are large, oblate-shaped, the color of the epicarp is cherry to purple, that of the mesocarp pink to lilac, they taste sweet, and show adequate firmness and quantity of ascorbic acid. The fruit has three fibrous endocarps, is cone to triangular-shaped and has one to two embryos. The embryo is cream colored without endosperm, the cotyledons are bent at the apex and the radicle is present at the other side . It is protected by a thin brown colored integument.Conclusions: Variation was observed in the morphological characteristics. The fruits have food potential and quality for export.